REAKSI OFENSIF RUSIA DALAM MENGHADAPI NATO PASCA KONFLIK KRIMEA TAHUN 2014-2017 - Syafitri Ramadhani; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to illustrate the phenomena occurring in Eastern Europe, especially Russia and Ukraine, as well as NATO involvement in it. Russia and NATO have a long and quite dynamic relationship. NATO continues to increase its military activity in Eastern Europe and it is getting closer to the Russian border. NATO carried out a series of military activities because it wanted to limit the hegemony of Russia in Eastern Europe especially after the annexation of the Crimean Peninsula. This research theoretically has built by using Kenneth Waltz NeoRealism perspective on International Relations and supported by National Security from Barry Buzan. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods. This research also using nation-state as the level of analyze. This study aims to describe the condition of Russia's security dilemma in deciding NATO's actions as defensive or offensive. A defensive reaction may occur if Russia never do counter attack. An Offensive reaction in the security strategies adopted by Russia to deal with NATO could shape the Balance Of Power. Russia chooses offensive actions in return and counterattack to deal with NATO Keywords : Security Dilemma, Balance Of Power, NATO, Eastern Europe